Pengaruh faktor-faktor kependudukan dan kontribusi sektor pertanian terhadap pertumbuhan ekonomi pada kabupaten/kota di Provinsi Jambi - Tri Utari; Junaidi Junaidi; Hardiani Hardiani (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2019)
This research aims to analyze the state of population growth, dependency ratio, labor force participation rate, contribution of the agricultural sector and economic growth in regencies/cities in Jambi Province. In addition, it also analyzes the influence of population growth, the dependency ratio, the level of labor force participation and the contribution of the agricultural sector to economic growth in regencies/cities in Jambi Province in 2012-2017. The method of analysis in this research is panel data analysis with the fixed effect method. The results of the study provide the conclusion that population growth and the dependency load ratio have a positive and significant effect on economic growth in regencies/cities in Jambi Province. The level of labor force participation and the contribution of the agricultural sector have no significant effect on economic growth in the regencies/cities of Jambi Province. Keywords: Population Growth, Dependency Ratio, Labor Force Participation Rate, Agricultural Sector Contribution, and Economic Growth.